Developing Students’ Character Through the Integration of Islamic Values in Mathematics Learning - Setiawan Setiawan; Saifullah Idris; Al Husaini M. Daud (SAINTIS Publishing, 2025)
This research aims to analyze the role of the integration of Islamic values in mathematics learning on the formation of students' character. Through a literature study approach, this research highlights how values such as honesty, justice, responsibility, hard work, and awareness of the greatness of God can be applied contextually in the mathematics learning process. The results of the study show that the integration of these values not only improves students' academic understanding, but also strengthens their moral and spiritual aspects. Mathematics learning based on Islamic values is able to foster the character of students who are religious, honest, disciplined, and able to work together. However, there are challenges in implementation, such as limited time, lack of teacher training, and the absence of a systematic learning model. Therefore, it is necessary to develop a curriculum and learning strategies that are able to accommodate the incorporation of Islamic values in mathematics education effectively.